Disaster in Sufi Interpretation: Dialecticalising the Sufistic Trilogy of Abdul Qadir al-Jilani, Ibn ’Arabi and Achmad Asrori al-Ishaqi - Ainul; Chafid; Hadi (Universitas Nahdlatul Ulama Surabaya, 2023)
The phenomenon of disaster is an inseparable part of human life. The understanding of it is often considered as a will of God or a natural occurrence, which consequently gives a non-anticipatory and desperate perspective. This study aims to reveal the articulation of disaster according to the idea of the Qur'an based on Sufi interpretation by dialecticism, the interpretations of Abdul Qadir al-Jilani, Ibn 'Arabi, and Achmad Asrori al-Ishaqi, from now on referred to as the